Inventaires de bibliothèques normandes : l’intérêt des listes tardives - Marie-Pierre Laffitte (Tabularia)
The archives of the library of Jean-Baptiste Colbert permit us to reconstruct a large part of the collections of the Norman cistercian abbeys and identify 350 manuscripts that Etienne Baluze purchased for the Minister between 1677 and 1683. Now preserved in the National Library of France, these volumes come from the Abbeys of Mortemer, Savigny, La Noë, Foucarmont and Bonport. They form a coherent group, dating mainly from the ninth to the fourteenth century, which deserves a thorough textual and codicological study.